2022
DOI: 10.1590/0001-3765202220211103
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison between antimicrobial and antibiofilm effects of Green Propolis and Baccharis dracunculifolia against Staphylococcus pseudintermedius isolate

Abstract: Staphylococcus pseudintermedius is the leading cause of canine pyoderma.Honeybee products are common to treat this and other types of infections. High average annual population loss of bees has been observed. This study evaluated antibacterial and antibiofilm profile of Green Propolis and Baccharis dracunculifolia against S. pseudintermedius and the chemical similarities among both. Ethanolic extracts were produced and chemically characterized. The isolates were subjected to treatment with the extracts in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Baccharis dracunculifolia (B. dracunculifolia) is a domestic plant which is widely used as an immunomodulator and an anti-bacterial and anti-diabetic agent, but it possesses many other properties [10,11]. Several studies have evaluated the medicinal actions of B. dracunculifolia, especially its anti-microbial effects [12][13][14]. Dos Santos et al reported the anti-inflammatory effects of B. dracunculifolia leaves extract on a paw edema model, which is induced by carrageenan and formalin [15].…”
Section: Baccharis Dracunculifolia Essential Oil (Bd-eo)mentioning
confidence: 99%
“…Baccharis dracunculifolia (B. dracunculifolia) is a domestic plant which is widely used as an immunomodulator and an anti-bacterial and anti-diabetic agent, but it possesses many other properties [10,11]. Several studies have evaluated the medicinal actions of B. dracunculifolia, especially its anti-microbial effects [12][13][14]. Dos Santos et al reported the anti-inflammatory effects of B. dracunculifolia leaves extract on a paw edema model, which is induced by carrageenan and formalin [15].…”
Section: Baccharis Dracunculifolia Essential Oil (Bd-eo)mentioning
confidence: 99%
“…Hydroalcoholic extract (70%) of dried leaves showed antimicrobial activity against Staphylococcus pseudintermedius, with MIC of 0.312 mg/ml and MBC of 2.5 mg/ml, in addition to having the ability to inhibit biofilm formation in vitro (Barbosa et al, 2022). This activity may be related to phenolic acid derivatives and flavonoids (Barbosa et al, 2022). The commercial hydroalcoholic extract of B. dracunculifolia was obtained from Ciclo Farma Indústria Química Ltda (Serrana, SP, Brazil), with the majority of artepillin C (Figure 5), rutin, and caffeic acid (Supplementary Figure S4) has been evaluated by Timbé et al (2021), presenting antimicrobial activity against all tested bacteria, with the highest inhibition halo for B. cereus (20.5 mm).…”
Section: Extractmentioning
confidence: 99%
“…Hydroalcoholic extract (70%) of dried leaves showed antimicrobial activity against Staphylococcus pseudintermedius , with MIC of 0.312 mg/ml and MBC of 2.5 mg/ml, in addition to having the ability to inhibit biofilm formation in vitro ( Barbosa et al, 2022 ). This activity may be related to phenolic acid derivatives and flavonoids ( Barbosa et al, 2022 ).…”
Section: Pharmacology and Bioactivitymentioning
confidence: 99%
See 2 more Smart Citations